Study the 1D quasi unsteady flow in simulating of sediment transport in Galing river by using hec-ras - Mohamad Hanif, Hamzah (2014)
Sedimentation comes from the sediment transport, which involved the rock, gravel, sand, silt, clay and other natural sources where it is caused by the erosion in the river. In my study, it is essential to make a research about the physical of the Galing River that can influence the simulating of sediment transport rate where can effect of Urban Land Uses and Stream-water. River bed changes, prediction in this study leans post uses 1 D modelling sediment provided by Hydrologic Engineering Canter's River Analysis System (HECRAS). This software allows performing one-dimensional quasi unsteady flow and sediment transport calculations. The data of cross section, flow discharge and sediment data are collected to run this software (HEC-RAS 4.1). Through this software we can the simulation the sediment transport pattern. There are 3 total bedload data that are used which is 0.1777 tonnes/m-day, 2.275 tonnes/m-day and 7.760 tonnes/m-day while the slope is 0.0001383. The result are predicting about a year and half with computation increment is 1 hour. The result shows that there are many sediment transport occur and it is compared to others method.The result of each approach, Meyer-Peter Muller method shows that there many locations that occur the erosion and sedimentation. The erosion occurs at the 150m, 700m and 1800m from the downstream while the sedimentation formed at station 7 and 16 where 600m and 1 lOOm from downstream. The Toffaleti method show that the erosion that occurs same with Meyer-Peter Muller method which is 150m, 700m and 1800m from downstream. The sedimentation that formed only at 1 location which is at station 7 where 600m from downstream. The Laursen method shows that the erosion has occurred in many locations which is 150m, 700m, 1150m and 1800m from downstream while the sedimentation that formed are same with Meyer-Peter Muller method.